What works in reducing inequalities in child health? - Roberts, Helen, 1949- (Policy Press, 2012)
The UK has a deservedly strong reputation for work on understanding social inequalities in health. But there is some way to go in ensuring that research and other types of knowledge are used to reduce inequalities in child health. This revised and updated edition of an important report looks at macro public policy interventions, community interventions, and individual level interventions in a variety of settings, and for a range of populations: infancy, early years, childhood and adolescence, and those with particular needs including looked after children. It considers 'what works' in practice. There are new case studies, updated research, and reference to cost effectiveness - particularly relevant for doing the right thing in a climate of austerity. Drawing on evidence from the UK and beyond, the book presents these in an accessible form not just for those who make decisions now, but also for the students of today who are the decision makers of tomorrow.